(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
William Faulkner(1897-1962) is the best known American writer for his complex narrative structure with extended descriptions and details . In other words, he creates complicated situations with a variety of characters, each has a different reaction to the situation . Consequently , leading to a complicated narrative structure not easily revealed. The hypothesis of the current study states that Faulkners in his short story " That Evening Sun Go Down " follows the normal narrative structure presented by Labove 1972. This study aims at analyzing the structure of Faulkner’s short story "That Evening Sun Go Down" . This story was published in 1931 . The analysis captures the writer’s intentions of fabricating the story through Labov’s narrative elements i.e. to comprehend the meaning which the writer wants to convey through its narrative components. The study reveals that applying a structural analysis is considered as a convincing way in understanding literary works and makes narration more comprehensible to the reader. The study reaches to the conclusion that Faulkners in his short story "That Evening Sun go down" has applied a normal narrative structure starting with the abstract and ending up with the coda .